2015
DOI: 10.3390/molecules200610435
|View full text |Cite
|
Sign up to set email alerts
|

KMUP-1 Attenuates Endothelin-1-Induced Cardiomyocyte Hypertrophy through Activation of Heme Oxygenase-1 and Suppression of the Akt/GSK-3β, Calcineurin/NFATc4 and RhoA/ROCK Pathways

Abstract: Abstract:The signaling cascades of the mitogen activated protein kinase (MAPK) family, calcineurin/NFATc4, and PI3K/Akt/GSK3, are believed to participate in endothelin-1 (ET-1)-induced cardiac hypertrophy. The aim of this study was to investigate whether KMUP-1, a synthetic xanthine-based derivative, prevents cardiomyocyte hypertrophy induced by ET-1 and to elucidate the underlying mechanisms. We found that in H9c2 cardiomyocytes, stimulation with ET-1 (100 nM) for 4 days induced cell hypertrophy and enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…IP3 can increase [Ca 2+ ] i and DAG can activate protein kinase C (PKC). Increased Ca 2+ and activation of PKC can lead to the early upregulation of proto-oncogenes, such as c-fos, c-myc, c-jun, and Egr-1; these genes encode proteins that act as third messengers that regulate the expression of target genes, which results in cardiac hypertrophy [ 20 ]. At the same time, Ang II could upregulate L-type-calcium channels, increasing calcium influx [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…IP3 can increase [Ca 2+ ] i and DAG can activate protein kinase C (PKC). Increased Ca 2+ and activation of PKC can lead to the early upregulation of proto-oncogenes, such as c-fos, c-myc, c-jun, and Egr-1; these genes encode proteins that act as third messengers that regulate the expression of target genes, which results in cardiac hypertrophy [ 20 ]. At the same time, Ang II could upregulate L-type-calcium channels, increasing calcium influx [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…PKCε‐specific chemical inhibitor have been reported to block heart failure , suggesting that PKCε plays a pivotal role in cardiac hypertrophy and heart failure. A recent study has shown that the hypertrophic effects of PKCε in the heart are associated with the activation of the AKT and ERK pathways , and suppression of AKT can attenuate the progress of cardiac hypertrophy . Consequently, activated AKT suppresses GSK3β, the negative regulator of cardiac hypertrophy, and activates NFAT transcriptional factor by dephosphorylation (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The signaling cascades of the mitogen activated protein kinase (MAPK) family, and phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt), are believed to be involved in cell-cycle regulation, apoptosis and inflammation (10,11). A growing body of evidence suggests that the Akt and extracellular signal-regulated (ERK) signaling pathway serve important roles in the development of cardiac hypertrophy and progression to HF.…”
Section: Introductionmentioning
confidence: 99%